Visitor's perception on recreation in Taiping Lake Garden - Ismail, Muhammad Hanif (2016)
Outdoor recreational experience is one of the services provided in many natural areas.This study is conducted in Taiping lake garden,Perak. This study aims to investigate perception of visitors towards Taiping Lake Garden as a recreation. Visitor perception toward the criteria of recreation tourist attraction in Taiping Lake Garden was captured through a self administered questionnaire.Different group of respondent are categorized by age,gender,current employment and education level.The respondent were selected based on a convenient sampling technique.The result show that,Taiping Lake Garden did posssed all the attributes to be a recreation and tourist attraction.Descriptive analysis was used to asses the perception level of visitor.The studies found that ,majority of respondent are local and frequently come to Taiping Lake Garden.Most of them came for sightseeing. High quality open space,park and green areas are the most attraction of tourist attraction considered by visitor.Overall,visitor‟s perception level are moderate. Management need to improve the attributes on Taiping Lake Garden to attract more tourist and local visitor.